A method of lowering the background in low-level radio-activity measurements. (November 2020) - Li, Yan; Zhao, Hongtao; Zhao, Xiaowen; Wu, Peng
Abstract: This paper discusses the main source of background in detecting radioactivity of low-level radiation and the methods to reduce the background in practical application.